Revised species checklist of the Paracolletinae (Hymenoptera, Colletidae) of the Australian Region, with the description of new taxa - Almeida, Eduardo A. B. (Zootaxa, 2008)
Colletid bees are widely distributed, but most of their diversity is found in southern continents, particularly Australia and South America. A major obstacle for the classification of Colletidae has been the lack of a well-resolved phylogenetic hypothesis encompassing representatives from all the main lineages of this family. A molecular phylogenetic study recently completed shed light on the subfamilial delimitation and relationships within Colletidae, and included a thorough enough sampling of Paracolletinae that genus-level classification could be evaluated. In this article a revised genus-level classification is presented for the Australian Paracolletinae, an attempt to make it more congruent with the phylogenetic relationships, as well as consistent with the classification of the South American paracolletine generic classification. According to the classification proposal presented here, Paracolletinae comprise 425 species, 298 of them endemic to the Australian Region. All subgenera of Leioproctus and of Paracolletes are elevated to the level of genus, thus raising the number genera occurring in the Australian Region to 25. According to a recent phylogenetic analysis of Colletidae, the Australian genus Callomelitta does not form a monophyletic group with the remaining genera of Paracolletinae. Callomelitta is hence removed from Paracolletinae and placed on a subfamily of its own, Callomelittinae, subfamily nov. Additionally, a new species of the Australian Paracolletinae genus Andrenopsis Cockerell is described as Andrenopsis michenerianus, sp.n..